YouTube Influencer: How Source Credibility and Information Quality Influence Destination Image and Visit Intention of Young Travelers? - Angelina Alice Laurance; Serli Wijaya; Sienny Thio (Jurnal Manajemen Indonesia, 2023)
This study aims to analyze the effects of YouTube influencers’ source credibility and the information quality of the platform on destination image and young travellers’ intention to visit a destination. Stimulus-organism-response (SOR) theory was adopted to develop the tested research model. This study applied a quantitative approach where primary data was collected through online surveys to 198 YouTube subscribers who had watched the examined YouTube channels’ content. The PLS-SEM technique was utilized to assess the structural model in the study. The results of this study show that source credibility had a significant positive effect on information quality, destination image, and visit intention. The information quality positively affected destination image but did not directly impact the visit intention. Furthermore, the destination image significantly mediates the effect of source credibility and information quality on visit intention. This study enriches the literature on the relationships among source credibility, information quality, and how these credibility and information quality could influence the destination image and young travellers’ intention to visit a destination in an emerging country like Indonesia. Keywords— Destination Image; Information Quality; Source Credibility; Visit Intention: YouTube Influencer; Young Travelers.